2016
DOI: 10.4238/gmr.15038599
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome analysis of tobacco seedlings and identification of the early response gene network under low-potassium stress

Abstract: ABSTRACT. Tobacco is an economically important crop, and its potassium content can greatly affect the quality of tobacco leaves. However, the molecular mechanism involved in potassium starvation in tobacco has not been elucidated to date. In this study, Illumina (Solexa) sequencing technology was used to analyze the transcriptome of tobacco seedlings under low-potassium stress for 6, 12, and 24 h. After analysis, 107,824 assembled unigenes were categorized into 57 GO functional groups, and 31,379 unigenes (29.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…It was shown that although changes in K + supply (either short- or long-term) affected the expression of a large number of membrane transporter genes, but surprisingly only a few genes belonged to K + transporters that have been reported. Similar results were reported for Arabidopsis [ 31 ], wheat and rice [ 66 ], and model legume, M. truncatula [ 63 ]. Also, only three GhHAK5 genes and one GhKUP3 gene were induced by low K + in the roots of both grafts in this study ( Figure 6 a).…”
Section: Discussionsupporting
confidence: 84%
“…It was shown that although changes in K + supply (either short- or long-term) affected the expression of a large number of membrane transporter genes, but surprisingly only a few genes belonged to K + transporters that have been reported. Similar results were reported for Arabidopsis [ 31 ], wheat and rice [ 66 ], and model legume, M. truncatula [ 63 ]. Also, only three GhHAK5 genes and one GhKUP3 gene were induced by low K + in the roots of both grafts in this study ( Figure 6 a).…”
Section: Discussionsupporting
confidence: 84%
“…CPK13 specifically inhibits guard cell-expressed KAT2 and KAT1 shaker K + channels [ 85 ]. The results of a recent study [ 86 ] showed that two CDPKs are up-regulated in tobacco seedlings under low-K + stress, whereas OsCPK9 and OsCCaMK1 are down-regulated in rice root responses to K + deficiency [ 87 ].…”
Section: Molecular Mechanisms Of Calcium Signaling Involved In Plamentioning
confidence: 99%
“…In low potassium treated pear fruit, there multiple cytochrome P450 members were detected [34]. In low potassium treated tobacco, 3 cytochrome P450 members were also up-regulated [37]. The DEGs belong to cytochrome P450 family were also detected from potassium deficiency tomato [38], low-N polar [39], rice [40], sorghum [41] and wild barley [42].…”
Section: Discussionmentioning
confidence: 98%